Sociodemographic and foetal characterisitics of mothers with premature deliveries in Hospital Tuanku Jaafar Seremban, Negri Sembilan, Malaysia - Zaini, I.; Ghani, S.N.; Moy, Foong Ming (Faculty of Medicine, University of Malaya, 2008)
This is a retrospective case control study conducted between 1 January 2005 and 30 June 2006 at the Hospital Tuanku Jaafar, Seremban, Malaysia. The objective was to study the maternal sociodemographics and foetal characteristics associated with premature delivery. There were 387 cases selected universally and 387 controls selected by using systematic random sampling involving every 13 cases. The patients were women who had delivered their babies before 37 completed weeks, while the control were women who had term deliveries during the same period. Data were collected using structured questionnaire through secondary data. Results showed that having multiple pregnancies (OR=8.33, 95 CI: 2.91, 23.84), congenital abnormality (OR=4.6, 95 CI: 0.98, 21.84) and intrauterine growth retardation (OR=15.59, 95 CI: 3.69, 65.82) were the risk factors of premature delivery. Being an ethnic Indian also raised the odds (OR=1.67, 95 CI: 1.14, 2.43) but this was not significant in the multivariate analysis. Other sociodemographic characteristics did not contribute significantly to the risk factors for premature delivery in this sample. In conclusion, foetal characteristics were found to be significantly associated with premature delivery after adjustment for other confounding factors. (JUMMEC 2008; 11 (2): 59-65).